Sales Attrition Analysis using Sales of Product Life Cycle Framework: A Case Study in a Financial Institution - Anastasia Sorta Maria; Albert Surya Wanasida (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Employee attrition is a common issue for businesses that needs to be mitigated. This study aimed to determine the sales attrition causes in Bank Y at different life cycle stages and provide recommendations to reduce the attrition. A qualitative method with a case study approach was applied in this research. Data was collected using interviews, psychometric tests, and from internal documents. Following descriptive and psychometric analyses, the causes of sales attrition in stages 1, 2, and 3 were personality reasons, inability to meet the target, and not receiving a promotion, respectively. To resolve these issues, we proposed that Bank Y conduct profiling during the hiring process and work, train the new hires, and transform the KPIs and incentives systems based on the sales staff profile. This study provides practical strategies and valuable information for human resource management to reduce employee attrition.